Meta-synthesis of qualitative studies to explore fathers’ perspectives of their influence on children’s obesity-related health behaviors - Eunyoung Park; Myoungock Jang; Mi Sook Jung; Nondumiso Satiso Dlamini (BMC Nursing, 2024)
Abstract Background In nursing research and practice, there is a paucity of information about how fathers perceive their role in shaping their children’s health behaviors. Most studies on the parental factors affecting children’s health behaviors have focused on the role of mothers. However, recent studies showed that fathers’ health behaviors can influence those of their children. Therefore, the aim of this study was to synthesize existing qualitative studies to explore fathers’ perspectives regarding how they influence children’s obesity-related health behaviors. Methods We conducted a descriptive meta-synthesis. To retrieve relevant articles, we used databases including PubMed, CINAHL, and Web of Science. Only qualitative studies published in English-language peer-reviewed journals, targeting fathers of children aged 2–18 years, and focusing on fathers’ perspectives were included. All the quotes collected from the studies were reviewed and coded, and thematic analysis was used to derive themes. Results Article screening and review yielded a total of 13 qualitative studies, from which the following themes emerged: (1) fathers’ parenting practices and role-modeling behaviors, (2) fathers’ roles in their relationships with their family members, and (3) fathers’ resource-seeking behaviors and contributions to their home food environment. Fathers were aware that their parenting practices and role-modeling behaviors could influence their children’s health behaviors. Furthermore, fathers recognized the importance of their relationships with family members, which was reflected in their family roles; that is, whether they took responsibility for childcare and household work, whether their parenting practices were similar to those of their spouses, and whether they involved their children in their activities. Fathers also reported their resource-seeking behaviors as well as their contribution to the home food environment, which affected their children’s health behaviors. Conclusion Fathers’ perspectives on their influence on children’s health behaviors reveal their unique paternal role in influencing children’s health behaviors. Fathers’ perspectives could be incorporated into future nursing research to examine the relationship between fathers’ roles and children’s health behaviors to develop better health intervention programs.